Capacity building for scaling agronomic innovations in the polders of the coastal zone of Bangladesh - Bhattacharya, Jayanta; Mondal, Manoranjan; Batas, Mary Ann; Parvin, Roksana; Ray, Amal; Rahman, Mahabubur; Vhadra, Shapon (2024)
Capacity building is crucial for scaling agronomic innovations within farming communities that enhance farmers' skills, knowledge, and resources to adopt new technologies and practices. Capacity building also fosters collaboration among farmers, researchers, and extension agents, facilitating the exchange of ideas and best practices. It also helps communities access funding, markets, and policy support, creating an enabling environment for innovation to thrive. Ultimately, strengthening the capacity of farmers leads to improved food security, economic development, and adaptability to changing climate conditions, ensuring that communities can effectively respond to future challenges. Work package 1 of the Asian Mega Delta initiative organized 12 events regarding crop and water management, mechanization and nutrition awareness among different stakeholders of national and international level. Total 4834 stakeholders were attended in these events in which 33% were women and 13 % were youth. These capacity building program might be an eye-opening step to influence the farming community, community leaders involved in water management (WMOs), agricultural technology dissemination personnel and the policymakers to adopt appropriate policies necessary to scale agricultural innovations across the coastal polder zone of Bangladesh.